GENDER RELATIONS IN THE HADITH "WOMEN AS A SOURCE OF FITNAH" - Fathan Akbar, Andre (Al-Imtaz: Jurnal Keilmuan Ushuluddin, 2024)
Along with the development of the times from time to time, issues related to gender issues continue to emerge and develop, one of the factors for the emergence of gender equality issues is because of the understanding of religious propositions that are less complete and comprehensive, giving the impression of discrimination against women. The purpose of this study is to find out how gender relations in the hadith of women as fitnah, as well as to understand the meaning of the hadith as a whole and thoroughly. Through a qualitative method with library research, the results of this study explain that slander is not only from the woman's side, but there are gender relations in it, namely slander or ugliness can be from men or women, so it is not right if this tradition is used to discriminate against women, that men or women all have the potential to make mistakes or ugliness.Keywords: Hadith, Relationship, Gender, Fitnah.